Steam Reforming of Dimethyl Ether by Gliding Arc Gas Discharge Plasma for Hydrogen Production - 王保伟 孙启梅 吕一军 杨美琳 闫文娟 (Chinese journal of chemical engineering, 2014)
Gliding arc gas discharge plasma was used for the generation of hydrogen from steam reforming of dimethyl ether （DME）. A systemic procedure was employed to determine the suitable experimental conditions. It was found that DME conversion first increased up to the maximum and then decreased slightly with the increase of added water and air. The increase of total feed gas flow rate resulted in the decrease of DME conversion and hydrogen yield, but hydrogen energy consumption dropped down to the lowest as total feed gas flow rate increased to 76 ml. min^-1. Larger electrode gap and higher discharge voltage were advantageous. Electrode shape had an important effect on the conversion of DME and production of H2- Among the five electrodes, electrode 2# with valid length of 55 mm and the radian of 34 degrees of the top electrode section was the best option, which enhanced obviously the conversion of DME.